2020
DOI: 10.1371/journal.pone.0240583
|View full text |Cite
|
Sign up to set email alerts
|

Pre-lacteal feeding practices and associated factors among mothers of children aged less than 12 months in Jinka Town, South Ethiopia, 2018/19

Abstract: Background Pre-lacteal feeding is one of the major harmful practices being faced while feeding the newborns. Although it affects child health, little is known about the extent of the problem and its contributing factors in the study area. Therefore, this study aimed to figure the prevalence of pre-lacteal feeding practices and associated factors among mothers of children aged less than 12 months in Jinka Town. Methods A community-based cross-sectional study was conducted at Jinka Town from March 1 to 30, 2019.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
3
25
4
Order By: Relevance
“…This proportion is comparable with findings from east Wollega zone (5.9%), 30 Ambo district (9.7%), 31 and Gonder town (8.2%) Ethiopia. 32 However, the current finding is lower than study results done in different parts of Ethiopia, 15% in Bahirdar city, 33 15.9% in Benishangul-gumuz region, 34 17.2% in Axum town, 35 and 16.8% in Debre birhan town. 36 The study results from lowand middle-income countries also report higher magnitude of pre-lacteal feeding, Nigeria (49.8% in urban and 66.4% in rural), 37 Kenya (26.8%), 38 in south Sudan (53%) 39 and in Himachal Pradesh, India (49.5%).…”
Section: Discussioncontrasting
confidence: 80%
“…This proportion is comparable with findings from east Wollega zone (5.9%), 30 Ambo district (9.7%), 31 and Gonder town (8.2%) Ethiopia. 32 However, the current finding is lower than study results done in different parts of Ethiopia, 15% in Bahirdar city, 33 15.9% in Benishangul-gumuz region, 34 17.2% in Axum town, 35 and 16.8% in Debre birhan town. 36 The study results from lowand middle-income countries also report higher magnitude of pre-lacteal feeding, Nigeria (49.8% in urban and 66.4% in rural), 37 Kenya (26.8%), 38 in south Sudan (53%) 39 and in Himachal Pradesh, India (49.5%).…”
Section: Discussioncontrasting
confidence: 80%
“…In this study, we obtained that institutional delivery and delayed ANC attendance were significantly associated with prelacteal feeding practice in Eastern Africa. In Eastern Africa, those mothers who deliver in health facilities decreased the practice of prelacteal feeding by 58%, in line with studies conducted in Ethiopia 50 , 51 systematic review and meta-analysis. 52 Since the mother who delivers in a health facility has a strong opportunity to obtain postnatal therapy from healthcare practitioners on the impact of prelacteal feeding, good position, and an attachment to breastfeeding.…”
Section: Discussionsupporting
confidence: 72%
“…This result is higher than that of a study in East Africa (3) and meta-analysis studies in Ethiopia (4,11). Moreover, the present finding is higher than the previous studies in southern (5,6) and northern part of Ethiopia (8,9,15), as well as it supports a spatial and multilevel study in Ethiopia reported that the Afar region has the greatest rate of prelacteal feeding (10). The different between the current study and the previous studies could be attributed to regional and ethnic differences in traditional practices.…”
Section: Discussioncontrasting
confidence: 96%
“…Mothers who give birth at health institutes were less practicing pre-lacteal feeding than those of home delivery. This finding is in line with the previous studies (3,4,6,7,(10)(11)(12).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation